Classical Political Economy and the Evolution of Central Banks: Endogenous Money and the Fiscal-Military State. (December 2018) - Vernengo, Matías
The paper analyzes briefly the changing ideas on the role of money and banks from William Petty to Thomas Tooke, including the works of Adam Smith, David Ricardo, and Karl Marx. It analyzes the role of ideas in shaping the evolution of central bank regulation. Particular importance is given to the Bank of England's inconvertibility period, from 1797 to 1821, and the ensuing debate in shaping Robert Peel's Bank Act of 1844, which is often seen as the birth of modern central banking. The importance of the Say's Law, and the inexistence of an alternative theory of the determination of output, is shown to play an essential role in the policy prescriptions of the so-called Bullionist authors, who won the debates that shaped central banking practices in the nineteenth century. The paper concludes with a brief analysis of what is a central bank according to the dominant (marginalist) mainstream of the profession, and what an alternative conception based on what may be termed classical-Keynesian political economy would be. JEL Classification: B10, N20, E58